Altered structure of cortical sulci in gilles de la Tourette syndrome: Further support for abnormal brain development. Issue 5 (26th March 2015) - Muellner, Julia; Delmaire, Christine; Valabrégue, Romain; Schüpbach, Michael; Mangin, Jean‐François; Vidailhet, Marie; Lehéricy, Stéphane; Hartmann, Andreas; Worbe, Yulia
Abstract Gilles de la Tourette syndrome is a neurodevelopmental disorder characterized by the presence of motor and vocal tics. We hypothesized that patients with this syndrome would present an aberrant pattern of cortical formation, which could potentially reflect global alterations of brain development. Using 3 Tesla structural neuroimaging, we compared sulcal depth, opening, and length and thickness of sulcal gray matter in 52 adult patients and 52 matched controls. Cortical sulci were automatically reconstructed and identified over the whole brain, using BrainVisa software. We focused on frontal, parietal, and temporal cortical regions, in which abnormal structure and functional activity were identified in previous neuroimaging studies. Partial correlation analysis with age, sex, and treatment as covariables of noninterest was performed amongst relevant clinical and neuroimaging variables in patients. Patients with Gilles de la Tourette syndrome showed lower depth and reduced thickness of gray matter in the pre‐ and post‐central as well as superior, inferior, and internal frontal sulci. In patients with associated obsessive‐compulsive disorder, additional structural changes were found in temporal, insular, and olfactory sulci. Crucially, severity of tics and of obsessive‐compulsive disorder measured by Yale Global Tic severity scale and Yale‐Brown Obsessive‐Compulsive scale, respectively, correlated with structural sulcal changes in sensorimotor, temporal, dorsolateral prefrontal, and middle cingulate cortical areas. Patients with Gilles de la Tourette syndrome displayed an abnormal structural pattern of cortical sulci, which correlated with severity of clinical symptoms. Our results provide further evidence of abnormal brain development in GTS. © 2015 International Parkinson and Movement Disorder Society